ANALISIS PENDAPATAN NELAYAN TRADISIONAL DAN MODERN DI KABUPATEN ACEH SELATAN - Yasrizal Yasrizal (Universitas Teuku Umar, 2017)
The main objective of this study was to determine the factors that affect the income of fishermen in Great Aceh. This study uses primary data is data that is obtained from the distribution of questionnaires to 95 respondents. Data were tested and analyzed using Multiple Linear Regression Model (Model Regresi linier Berganda) technique with Ordinary Least Square (OLS). The results of the analysis indicate that the traditional fishermen Capital (M), The amount of labor (L) significantly affects the income of fishermen in Great Aceh, the results of the analysis showed the modern fisherman working capital (M) and the number of days at sea (J) a significant effect on the income of fishermen. From the analysis that has been carried out on several criteria that capital should be used with an increase in working capital, of course the results obtained should be greater using of working capital efficiency improvements can be done by calculating the operational cost needs better. Limitations of venture capital or investment can also complicate fisheries fishermen increase economic activity. Because the government can help the fishermen by enhancing the functions of microfinance institutions and cooperatives pro fisherman and build Business Group (KUB) for fishermen, such as through ownership of the means of collective arrests